2007
DOI: 10.1186/1471-2350-8-24
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral-mediated correction of methylmalonyl-CoA mutase deficiency in murine fibroblasts and human hepatocytes

Abstract: Background: Methylmalonic acidemia (MMA), a common organic aciduria, is caused by deficiency of the mitochondrial localized, 5'deoxyadenosylcobalamin dependent enzyme, methylmalonyl-CoA mutase (MUT). Liver transplantation in the absence of gross hepatic dysfunction provides supportive therapy and metabolic stability in severely affected patients, which invites the concept of using cell and gene delivery as future treatments for this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 39 publications
(50 reference statements)
1
18
0
Order By: Relevance
“…Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) was done with 35 mg of clarified liver extract and transferred to nylon membranes. Western blot analysis was performed with a rabbit polyclonal antibody against murine Mut at a 1:500 dilution (Chandler et al, 2007b) and mouse monoclonal anti-OxPhos (oxidative phosphorylation) complex III core II antibody (A-11143; Invitrogen, Carlsbad, CA) at a 1:4000 dilution; incubation was for 3 hr. Horseradish peroxidase (HRP)-conjugated goat anti-rabbit antibody (1858415; Pierce Protein Research Products/Thermo Scientific) at a 1:10,000 dilution or HRP-conjugated goat anti-mouse antibody (1858413; Pierce Protein Research Products/Thermo Scientific) at a 1:30,000 dilution was incubated for 1 hr.…”
Section: Western Blottingmentioning
confidence: 99%
“…Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) was done with 35 mg of clarified liver extract and transferred to nylon membranes. Western blot analysis was performed with a rabbit polyclonal antibody against murine Mut at a 1:500 dilution (Chandler et al, 2007b) and mouse monoclonal anti-OxPhos (oxidative phosphorylation) complex III core II antibody (A-11143; Invitrogen, Carlsbad, CA) at a 1:4000 dilution; incubation was for 3 hr. Horseradish peroxidase (HRP)-conjugated goat anti-rabbit antibody (1858415; Pierce Protein Research Products/Thermo Scientific) at a 1:10,000 dilution or HRP-conjugated goat anti-mouse antibody (1858413; Pierce Protein Research Products/Thermo Scientific) at a 1:30,000 dilution was incubated for 1 hr.…”
Section: Western Blottingmentioning
confidence: 99%
“…This exon encodes the putative substrate-binding pocket in the methylmalonyl-CoA mutase enzyme. The mutant allele does not produce detectable RNA, protein, or enzymatic activity (Chandler et al, 2007). Homozygous knockout animals on a mixed (C57BL/6 ϫ 129Sv/Ev) background display a neonatal lethal phenotype and perish within the early neonatal period.…”
Section: Murine Model Of Methylmalonic Acidemiamentioning
confidence: 99%
“…Previous studies have demonstrated that the cytomegalovirus (CMV)-Mut bifunctional adenovirus (Ad-Mut-GFP) used in these experiments expressed enhanced green fluorescent protein (eGFP) in vivo and could correct the propionate metabolic defect in Mut Ϫ/Ϫ murine embryonic fibroblasts (MEFs) and primary hepatocytes derived from a mut 0 patient (Chandler et al, 2007). Another adenovirus, carrying only the Rous sarcoma virus (RSV) eGFP expression cassette in the E3 region (Ad-GFP), was used as an injection control.…”
Section: Adenoviral Vector Construction and Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with a mut(0) phenotype had a severe phenotype and early and more severe CRF than patients with mut-/cblA phenotype. Chandler et al (2007) reports successful use of adenoviral mediated gene therapy for methylmalonic aciduria in murine models and human patients with MUT gene mutation. Yang et al (2006) and other authors report that in China methylmalonic acidurias is more commonly associated with homocysteinemia.…”
Section: Review Of Literaturementioning
confidence: 99%